2019
DOI: 10.1002/jocb.424
|View full text |Cite
|
Sign up to set email alerts
|

Triangulating Creativity: Examining Discrepancies Across Self‐Rated, Quasi‐Expert‐Rated and Verbalized Creativity in Arts‐based Learning

Abstract: This convergent mixed methods study examined the triangulation of self-rated, quasi-expert-rated and verbalized creativity in students enrolled in a year-long photography program. The quantitative data included self-report scales in creativity, and ratings of creativity in students' photography. The qualitative data included student interviews reflecting on their photographs and verbalizing their beliefs about creativity. The data were first analyzed separately and then merged for analysis to determine possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Some research has shown high levels of agreement between experts and novices (Freeman et al, 2015), but sometimes agreement is better when the novices have some prior knowledge (Kaufman et al, 2013, Study 1;Plucker et al, 2009). Other studies have shown disagreement between experts and novices (Katz-Buonincontro et al, 2020;Kaufman et al, 2013, Study 2). Most research on creativity uses expert raters, and we recommend that practice is followed in future research, although experts can disagree with each other as well (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has shown high levels of agreement between experts and novices (Freeman et al, 2015), but sometimes agreement is better when the novices have some prior knowledge (Kaufman et al, 2013, Study 1;Plucker et al, 2009). Other studies have shown disagreement between experts and novices (Katz-Buonincontro et al, 2020;Kaufman et al, 2013, Study 2). Most research on creativity uses expert raters, and we recommend that practice is followed in future research, although experts can disagree with each other as well (cf.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the impact of arts-based interventions on competence development, reliable observational data and tested scales are necessary. Sound psychometry is needed to establish contemporary measurement tools for outcomes that arts-based methods typically address [ 149 ]. The high-quality studies examined in this review predominantly employ established measurement instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys and interviews were generally used in mixed-method studies (e.g., Alt & Raichel, 2020;Byrge & Tang, 2015). In addition, the observer ratings, anecdotal records, written plans were also used (e.g., Atwood-Blaine et al, 2019;Katz-Buonincontro et al, 2020b). An open-ended survey was used in the research that applied the qualitative method (Lemons, 2010).…”
Section: Methodsmentioning
confidence: 99%